2021
DOI: 10.3906/sag-2012-31
|View full text |Cite
|
Sign up to set email alerts
|

Tendon of Flexor Carpi Radialis in carpal tunnel: a radiologic and cadaveric study

Abstract: Background/Aim: Carpal tunnel is an important anatomical passage that carries the flexor tendons into the hand. As there is still no consensus about its contents among the anatomy textbooks, the main purpose of this study was to identify the relations of the flexor carpi radialis tendon in the carpal tunnel. Materials and methods: This retrospective study was completed in April 2018 at authors' university's hospital. Seventy-four female and 44 male patients' wrists without any pathology were examined by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Botelho and Ferreira 32 evaluated the craniovertebral junction magnetic resonance images of patients with chiari malformation and basilar invagination and a control group of healthy individuals; the mean angle in the control group was 126 ± 9.40 degrees, with a minimum of 103 degrees and a maximum of 148 degrees. In a study by Ferreira and Botelho, 33 the mean angle in the control group was 126.20 ± 9.68 degrees, whereas a study by Erçakmak Güneş and Vatansever 10 reported mean angles of 153.46 ± 9.13 degrees in females and 149.93 ± 8.60 degrees in males. The mean angles found in this study between the clivus and the foramen magnum are therefore consistent with the literature, except for Erçakmak Güneş and Vatansever, 10 who suggested that their higher values may be due to social and morphometric differences and that such larger angles should be considered in surgical approaches.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Botelho and Ferreira 32 evaluated the craniovertebral junction magnetic resonance images of patients with chiari malformation and basilar invagination and a control group of healthy individuals; the mean angle in the control group was 126 ± 9.40 degrees, with a minimum of 103 degrees and a maximum of 148 degrees. In a study by Ferreira and Botelho, 33 the mean angle in the control group was 126.20 ± 9.68 degrees, whereas a study by Erçakmak Güneş and Vatansever 10 reported mean angles of 153.46 ± 9.13 degrees in females and 149.93 ± 8.60 degrees in males. The mean angles found in this study between the clivus and the foramen magnum are therefore consistent with the literature, except for Erçakmak Güneş and Vatansever, 10 who suggested that their higher values may be due to social and morphometric differences and that such larger angles should be considered in surgical approaches.…”
Section: Discussionmentioning
confidence: 91%
“…Xu and Gong 20 reported that the mean angle was 135.8 ± 9.2 degrees in a control group and 110.4 ± 15.8 degrees in patients with basilar invagination, whereas Nagashima and Kubota 31 reported an angle of 157.4 ± 7.5 degrees in female patients and 158.2 ± 9.8 degrees in male patients on direct radiographs taken in a neutral position. Botelho and Ferreira 32 and Ferreira and Botelho 33 reported angles of 148 ± 9.88 and 148.50 ± 10.10 degrees, respectively, and Erçakmak Güneş and Vatansever 10 reported a mean angle of 140.61 degrees in female patients and 141.28 degrees in male patients. The results of the current study are therefore consistent with the literature.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…2 ). 3 In 84% of cases, the trapezium-trapezoid junction joins the superior face of the tunnel. Before the tendon runs into the tunnel, it slides on a trajectory over the volar distal pole of the scaphoid.…”
mentioning
confidence: 99%